New high nuclearity carbonyl clusters - Tiozzo, Cristina <1980> (Alma Mater Studiorum - Università di Bologna, 2009)
The thesis reports the synthesis, and the chemical, structural and spectroscopic characterization of a series of new Rhodium and Au-Fe carbonyl clusters. Most new high-nuclearity rhodium carbonyl clusters have been obtained by redox condensation of preformed rhodium clusters reacting with a species in a different oxidation state generated in situ by mild oxidation. In particular the starting Rh carbonyl clusters is represented by the readily available [Rh7(CO)16]3- 9 compound. The oxidized species is generated in situ by reaction of the above with a stoichiometric defect of a mild oxidizing agents such as [M(H2O)x]n+ aquo complexes possessing different pKa’s and Mn+/M potentials. The experimental results are roughly in keeping with the conclusion that aquo complexes featuring E°(Mn+/M) < ca. -0.20 V do not lead to the formation of hetero-metallic Rh clusters, probably because of the inadequacy of their redox potentials relative to that of the [Rh7(CO)16]3-/2- redox couple. Only homometallic cluster s such as have been fairly selectively obtained. As a fallout of the above investigations, also a convenient and reproducible synthesis of the ill-characterized species [HnRh22(CO)35]8-n has been discovered. The ready availability of the above compound triggered both its complete spectroscopic and chemical characterization. because it is the only example of Rhodium carbonyl clusters with two interstitial metal atoms. The presence of several hydride atoms, firstly suggested by chemical evidences, has been implemented by ESI-MS and 1H-NMR, as well as new structural characterization of its tetra- and penta-anion. All these species display redox behaviour and behave as molecular capacitors. Their chemical reactivity with CO gives rise to a new series of Rh22 clusters containing a different number of carbonyl groups, which have been likewise fully characterized. Formation of hetero-metallic Rh clusters was only observed when using SnCl2H2O as oxidizing agent because. Quite all the Rh-Sn carbonyl clusters obtained have icosahedral geometry. The only previously reported example of an icosahedral Rh cluster with an interstitial atom is the [Rh12Sb(CO)27]3- trianion. They have very similar metal framework, as well as the same number of CO ligands and, consequently, cluster valence electrons (CVEs). .A first interesting aspect of the chemistry of the Rh-Sn system is that it also provides icosahedral clusters making exception to the cluster-borane analogy by showing electron counts from 166 to 171. As a result, the most electron-short species, namely [Rh12Sn(CO)25]4- displays redox propensity, even if disfavoured by the relatively high free negative charge of the starting anion and, moreover, behaves as a chloride scavenger. The presence of these bulky interstitial atoms results in the metal framework adopting structures different from a close-packed metal lattice and, above all, imparts a notable stability to the resulting cluster. An organometallic approach to a new kind of molecular ligand-stabilized gold nanoparticles, in which Fe(CO)x (x = 3,4) moieties protect and stabilize the gold kernel has also been undertaken. As a result, the new clusters [Au21{Fe(CO)4}10]5-, [Au22{Fe(CO)4}12]6-, Au28{Fe(CO)3}4{Fe(CO)4}10]8- and [Au34{Fe(CO)3}6{Fe(CO)4}8]6- have been isolated and characterized. As suggested by concepts of isolobal analogies, the Fe(CO)4 molecular fragment may display the same ligand capability of thiolates and go beyond. Indeed, the above clusters bring structural resemblance to the structurally characterized gold thiolates by showing Fe-Au-Fe, rather than S-Au-S, staple motives. Staple motives, the oxidation state of surface gold atoms and the energy of Au atomic orbitals are likely to concur in delaying the insulator-to-metal transition as the nuclearity of gold thiolates increases, relative to the more compact transition-metal carbonyl clusters. Finally, a few previously reported Au-Fe carbonyl clusters have been used as precursors in the preparation of supported gold catalysts. The catalysts obtained are active for toluene oxidation and the catalytic activity depends on the Fe/Au cluster loading over TiO2.